1995
DOI: 10.1042/bst023401s
|View full text |Cite
|
Sign up to set email alerts
|

Caged FEDA-ATP: a new tool in the measurement of ATP turnover during the in vitro motility assay

Abstract: In an attempt to distinguish between the various models of muscle contraction, attention has been focused upon calculation of the myosin crossbridge step-size (the distance moved during active interaction of a myosin head with acM per ATP molecule hydrolysed) using in virro motility assays. We have previously used a fluorescein derivative of ATP, FEDA-ATP as a potential probe for nucleotide turnover under in virro assay conditions [l].Although an array of myosin heads can be visualised in the presence of FEDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although we have carried out fewer measurements with other fluorophores, we have shown that the overall kinetics of interaction are similar for both REDA-ATP and Cy3-EDA-ATP. Also, we have introduced photoactivatable caged fluorescein in this manner and shown that the caged FEDA-ATP is a substrate for myosin (Jeffreys et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have carried out fewer measurements with other fluorophores, we have shown that the overall kinetics of interaction are similar for both REDA-ATP and Cy3-EDA-ATP. Also, we have introduced photoactivatable caged fluorescein in this manner and shown that the caged FEDA-ATP is a substrate for myosin (Jeffreys et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Conibeap; C.R. Bagshaw/FEBS Letters 380 (1996) [13][14][15][16] otides is likely to effect only the amplitude rather than the kinetics of observed intensity changes. The REDA-ADP-dissociation kinetics provide a test of the time resolution of the apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, we can now monitor displacement from a l-/~m segment of a synthetic myosin filament estimated to contain a few hundred sites with a time resolution of 0.1 s. Furthermore, the technique has made records much more reproducible owing to the lack of mechanical artefacts inherent to flow methods. The finding that ATP can be released photolytically without damage to the catalytic activity of myosin is a necessary prerequisite for the general use of flash photolysis and bodes well for studies using caged fluorescent ATP analogs [14]. We have initiated the sliding of actin in in vitro motility assays with this apparatus [15], but this process is more susceptible to damage from the free radicals released during photolysis and inclusion of thiol reagents is essential.…”
Section: Discussionmentioning
confidence: 99%